The Influence Of Leadership Style, Work Motivation And Work Discipline On The Performance Of Account Representatives Of KPP Pratama Sidoarjo Utara - Patmawati, Patmawati; Nanik Kustiningsih (Jurnal Ekonomi, 2024)
The North Sidoarjo Tax Office encounters difficulties in meeting its tax revenue targets due to variations in employee performance and insufficient work standards, although existing research presents mixed findings regarding the impact of these factors. This study aims to evaluate the effects of leadership style, work motivation, and work discipline on the performance of account representatives at KPP Pratama Sidoarjo Utara. The research considers a total population of 31 employees from KPP Pratama Sidoarjo Utara account representatives, with a sample size of 31 individuals selected through saturated sampling. A questionnaire serves as the primary tool for data collection, having undergone validity and reliability testing. The data analysis employs multiple linear regression. The findings indicate that (1) leadership style does not significantly affect the performance of KPP Pratama Sidoarjo Utara account representatives, (2) motivation positively influences their performance, and (3) work discipline also impacts the performance of KPP Pratama Sidoarjo Utara account representatives.